Special education unique leadership style: the concept - Nordin, Mohd Norazmi; Mustafa, Mohamad Zaid; Ibrahim, Badaruddin; Abdul Razzaq, Abdul Rasid; Mosbiran, Nor Fauziyana (2020)
Leadership style is often a hot topic in determining the stability of an organization. The leadership style practiced by the leader will push an organization to move with its own mold. If the right leadership style is practiced and appropriate to the situation, then the likelihood of seeing harmony in an organization is very high. With leadership style as well, the work environment will be determined according to the leadership mold practiced by leaders for an organization. Successful leadership can also shape the success of the organization it leads. Discussions related to these leadership styles go beyond the scope of a very broad range of fields. This is because leadership is needed for everything. Starting from the smallest leadership for yourself to the leadership of a country. As such, it is undeniable that education also requires effective leadership. Starting from the following reasons, it is certainly a great responsibility of educational leadership, especially to those who lead the school, to determine the appropriate leadership style in designing a good success for the school led.